Performance analysis of economic MPC with self-tuning terminal cost - Müller,MA; Angeli,D; Allgöwer,F (2014)
In this paper, we further analyze an economic model predictive control (MPC) algorithm with self-tuning terminal cost, which was recently proposed in [1]. It is shown that if a generalized terminal region constraint instead of a generalized terminal equality constraint is used, improved closed-loop asymptotic average performance bounds can be obtained. In particular, in contrast to the results in [1], these bounds can be obtained a priori. We discuss how the necessary parameters for the generalized terminal region setting can be calculated, and we illustrate our findings with a numerical example. © 2014 American Automatic Control Council.